Analisis Framing tentang Sepakbola dalam Playlist Justalk Episode 765 pada Channel Youtube Justinus Lhaksana - Tardha Widara Rochmansyah; Dr. Aning Sofyan, Drs., M.Si. (UNISBA Press, 2023)
Abstract. YouTube is a form of video-based social media that was released in 2005. YouTube is a video site that provides various information in the form of videos ranging from Music, Film, News and Information, Sports, Lifestyle, Gaming, and Vlogs. One of the content creators currently utilizing YouTube is owned by Justinus Lhaksana or known as coach Justin, who has approximately 500 thousand subscribers and has around 100 to 200 thousand more viewers in each of his content. This research uses descriptive qualitative research methods. Data analysis in this study used the Zhongdang Pan and Gerald M. Kosicki framing analysis model. The subject to be researched is a video entitled “JusTalk #765: JusTalk #765: Prancis keok, Lucky Aussie & Argen Kok Bisa Juara Grup” on Justinus Lhaksana's YouTube Channel with a duration of 10 minutes. Meanwhile, the object of this study is the framing method of the JusTalk episode 765 video. The data collection technique used in this study was observation. The research results from the JusTalk program presented football by showing a sharing session videos. Coach Justin delivered what was happening in football at the 2022 World Cup Qatar based on what he observed as a football observer. By using football framing analysis, it can be seen from various perspectives, starting from the progress of the match, the strategies of the two teams, to the composition of the players used by the two teams. However, there are pronouns and foreign languages that are used slightly towards satirical, such as using the word